KEPATUHAN PELAPORAN WAJIB PAJAK (STUDI KASUS DI JAKARTA BARAT DAN TANGERANG) - MERRY SUSANTI; SOFIA PRIMA DEWI; SUFIYATI SUFIYATI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research was to obtain factors that influence taxpayer reporting compliance in West Jakarta and Tangerang. Data collection method was conducted by distributing questionnaires to lecturers in West Jakarta and Tangerang. Questionnaires were distributed from April 3 to May 26, 2017. Data processing methods were performed using SPSS. The results showed that taxpayers' awareness and willingness to pay taxes have influence on taxpayer reporting compliance of lecturer in West Jakarta and Tangerang while tax sanction, fiscus service, know-ledge and understanding of taxation regulation, and perception on effectiveness of tax system have no influence on taxpayer reporting compliance of lecturer in West Jakarta and Tangerang.